Urinary Cell Adhesion Molecule 1 Is a Novel Biomarker That Links Tubulointerstitial Damage to Glomerular Filtration Rates in Chronic Kidney Disease - Hagiyama, Man; Nakatani, Yoshihisa; Takashima, Yasutoshi; Kato, Takashi; Inoue, Takao; Kimura, Ryuichiro; Otani, Tomoyuki; Sato, Yasufumi; Mori, Hideo; Arima, Shuji; Ito, Akihiko (Frontiers in Cell and Developmental Biology, 2019)
Cell adhesion molecule 1 (CADM1) is an immunoglobulin superfamily member strongly expressed on renal tubular epithelia in the urinary tract. Enzymatic cleavage of its ectodomain increases in chronic kidney disease (CKD), and is assumed to contribute to tubulointerstitial lesion formation. Because the cleaved ectodomain fragments are likely to be released into the urine, a sandwich enzyme-linked immunosorbent assay (ELISA) system for urinary CADM1 was developed using two anti-ectodomain antibodies. Urinary CADM1 concentrations in patients with CKD based on various forms of glomerulonephritis and nephropathy (n = 127) were measured. A total of 44 patients (35%) had elevated CADM1 concentrations over the normal upper limit (362 pg/mL), with a mean of 1,727 pg/mL. Renal biopsy specimens of all patients were pathologically scored for tubulointerstitial lesions using epithelial degeneration, interstitial inflammation, and fibrosis. There were no correlations between urinary CADM1 concentrations and pathological scores or any widely used renal markers, including glomerular filtration rate (GFR), but there was a weak inverse correlation between pathological scores and GFR (R2 = 0.292). Notably, this correlation gradually increased in patients with increasing CADM1 concentrations, and reached a maximum R2 (0.899) at a cutoff of 1,569 pg/mL. The results of this study suggest that urinary CADM1 is a useful marker indicating tubulointerstitial damage from elevated GFR levels in CKD.